On the Brink: Mapping the Last Strongholds of the Critically Endangered Flapper Skate (Dipturus intermedius) - Sophie L. Loca; Patrick C. Collins; Amy Garbett; Ryan McGeady; James Thorburn; Chris McGonigle (Ecology and Evolution)
ABSTRACT The flapper skate (Dipturus intermedius) is a Critically Endangered skate distributed throughout the NE Atlantic and requiring urgent conservation measures. Existing models of the flapper skate's distribution are not detailed enough to inform management. The aim of this study was to develop more highly resolved predictions of the skate's distribution across its range, building on existing studies to provide a comprehensive baseline for flapper skate presence. Location The NE Atlantic shelf region. A Bayesian spatial binomial GAMM was used to model the distribution of flapper skate across the NE Atlantic shelf. Following an exhaustive search of fisheries‐independent DATRAS catch records, skate presence was modelled as a function of environmental covariates and AIS fishing pressure data. Skate presence was highest in coastal areas approximately 40–50 km from shore, where fishing pressure and benthic productivity were low. A smoother for the bathymetry variable indicated presence was highest at depths of 100–200 m. Regions with the highest predicted probability of occurrence included the north and west coasts of Scotland, and the west coast of Ireland near Counties Clare and Galway. In contrast, very low support was given for presence in the southern and central North Sea, likely reflecting historical population collapse, as well as in deeper offshore waters beyond the shelf. This study presents the first large‐scale model of flapper skate presence across the NE Atlantic shelf that integrates both environmental and fishing pressure data, providing new baseline insights into habitat use in the North Sea and around Ireland. Three core regions of presence were identified, likely reflecting natural refugia from fishing and critical habitats (EFHs). Future research should prioritise these strongholds, focusing on identifying critical habitats to support focused management strategies.